Letter from Éamonn Duggan to friends and family, written during his detention in Lewes Prison, - Duggan, Éamonn, 1874-1936 (1917)
Duggan’s letter is marked as being ‘In lieu of a visit’ and is addressed to Phyllis [Morkan], Matt, Cissie Duggan and his fiancée May Kavanagh. Writing to Matt, Duggan refers to having passed his friend's message onto ‘all the boys, including De Valera’, his speech at his Court-martial, his feelings on receiving his sentence and the scattering of their group that contained Matt, Ned Daly and himself. In his letter to May Kavanagh he writes of how he will always be ‘identified with all those noble souls whose glorious self-sacrifice has illumined the sad pages of our Country’s history’. He assures her of his good spirits, his confidence that ‘bright days’ are coming for both himself and Ireland and progress in studying Irish. He also enquires about his friends who are fighting at the front. In his note to Phyllis Morkan he refers to the death of Ned Daly and the political changes in Ireland since his arrest. His letter is written on prison paper, which outlines the rules governing prisoner's correspondence; Duggan signs himself as Edmund.